HaCaT Cells as a Reliable In Vitro Differentiation Model to Dissect the Inflammatory/Repair Response of Human Keratinocytes. (17th December 2017) - Colombo, Irma; Sangiovanni, Enrico; Maggio, Roberta; Mattozzi, Carlo; Zava, Stefania; Corbett, Yolanda; Fumagalli, Marco; Carlino, Claudia; Corsetto, Paola Antonia; Scaccabarozzi, Diletta; Calvieri, Stefano; Gismondi, Angela; et al.
Abstract : Cultured primary human keratinocytes are frequently employed for studies of immunological and inflammatory responses; however, interpretation of experimental data may be complicated by donor to donor variability, the relatively short culture lifetime, and variations between passages. To standardize the in vitro studies on keratinocytes, we investigated the use of HaCaT cells, a long-lived, spontaneously immortalized human keratinocyte line which is able to differentiate in vitro, as a suitable model to follow the release of inflammatory and repair mediators in response to TNF α or IL-1 β . Different treatment conditions (presence or absence of serum) and differentiation stimuli (increase in cell density as a function of time in culture and elevation of extracellular calcium) were considered. ELISA and Multiplex measurement technologies were used to monitor the production of cytokines and chemokines. Taken together, the results highlight that Ca 2+ concentration in the medium, cell density, and presence of serum influences at different levels the release of proinflammatory mediators by HaCaT cells. Moreover, HaCaT cells maintained in low Ca 2+ medium and 80% confluent are similar to normal keratinocytes in terms of cytokine production suggesting that HaCaT cells may be a useful model to investigate anti-inflammatory interventions/therapies on skin diseases.